Insulin modulates emotional behavior through a serotonin-dependent mechanism - Martin, Hugo; Bullich, Sébastien; Martinat, Maud; Chataigner, Mathilde; Di Miceli, Mathieu; Simon, Vincent; Clark, Samantha; Butler, Jasmine; Schell, Mareike; Chopra, Simran; Chaouloff, Francis; Kleinridders, Andre; et al. (Molecular psychiatry, 2024)
Type-2 Diabetes (T2D) is characterized by insulin resistance and accompanied by psychiatric comorbidities including major depressive disorders (MDD). Patients with T2D are twice more likely to suffer from MDD and clinical studies have shown that insulin resistance is positively correlated with the severity of depressive symptoms. However, the potential contribution of central insulin signaling in MDD in patients with T2D remains elusive. Here we hypothesized that insulin modulates the serotonergic (5-HT) system to control emotional behavior and that insulin resistance in 5-HT neurons contributes to the development of mood disorders in T2D. Our results show that insulin directly modulates the activity of dorsal raphe (DR) 5-HT neurons to dampen 5-HT neurotransmission through a 5-HT 1A receptor-mediated inhibitory feedback. In addition, insulin-induced 5-HT neuromodulation is necessary to promote anxiolytic-like effect in response to intranasal insulin delivery. Interestingly, such an anxiolytic effect of intranasal insulin as well as the response of DR 5-HT neurons to insulin are both blunted in high-fat diet-fed T2D animals. Altogether, these findings point to a novel mechanism by which insulin directly modulates the activity of DR 5-HT neurons to dampen 5-HT neurotransmission and control emotional behaviors, and emphasize the idea that impaired insulin-sensitivity in these neurons is critical for the development of T2D-associated mood disorders.